Team Whoosh Generator 2015 WSGC Collegiate Rocket Competition - Johnson, Eric (Proceedings of the Wisconsin Space Conference, 2016)
The objectives of the 2015 Wisconsin Space Grant Consortium (WSGC) Collegiate Rocket Competition were to design and build a â€œboosted dartâ€ high-powered rocket to allow the dart stage to reach the highest possible apogee and to conform to design restrictions and added design objectives. The rocket was required to use a Cesaroni I-445 motor as specified by WSGC, use a flight data recorder provided by WSGC, and be safely recovered in a flyable condition by use of a parachute system. The dart was required to be an unpowered upper stage that drag separates from the booster without imparting momentum onto the dart. In addition to the altimeters already on board, a noncommercial data acquisition system was required to record data on the rotation of the rocket in the X, Y, and Z axes over time. Finally, the rocket was required to record downward facing video of the flight starting at the time of launch. Included in this report are design details considered, anticipated performance, photos of constructed components, and flight results.